Case report: Novel multi-exon homozygous deletion of ZBTB24 causes immunodeficiency, centromeric instability, and facial anomalies syndrome 2 - Long, Yan; Wang, Chenghan; Xiao, Jie; Huang, Yunhua; Ling, Xiaoting; Huang, Chaoyu; Chen, Ying; Luo, Jiaqi; Tang, Rongheng; Lin, Faquan; Huang, Yifang (Frontiers in Immunology, 2025)
Immunodeficiency, centromeric instability, and facial anomalies syndrome (ICF) is a rare genetic disease characterized by hypogammaglobulinemia, T cell immune deficiency with age, pericentromeric hypomethylation, facial abnormalities, and intellectual disability. This study aimed to investigate the phenotype and immune function of a girl with ICF2, identify her genetic defect, and explore the potential pathogenic mechanisms of the disease. We identified a homologous deletion mutation in this girl, which involves exons 1-5 and part of introns 1 and 6 of the ZBTB24 gene (NG_029388.1: g.2831_18,995del). This ZBTB24 variant produces a severely truncated ZBTB24 protein that lacks the BTB, A-T hook and eight zinc fingers. The above changes may lead to abnormal transcriptional function of the ZBTB24 protein. Karyotype analysis showed fragile sites and entire arm deletions were detected on chromosomes 1 and 16 and triradials on chromosome 16. The novel multi-exon deletion of ZBTB24 causes immunodeficiency, severe pneumonia and centromeric instability in the patient. During the follow-up, the patient’s pneumonia continued to progress despite receiving intravenous immunoglobulin (IVIG) replacement and anti-infective therapy. These results indicated that this novel multi-exon deletion variant of ZBTB24 may be the genetic etiology of ICF2. The discovery of this novel mutation expands the mutation spectrum of the ZBTB24 gene and improves our understanding of the molecular mechanisms underlying ICF.